1-phenyl 2-thiourea (PTU) activates autophagy in zebrafish embryos. Issue 5 (4th May 2021) - Chen, Xiang-Ke; Kwan, Joseph Shiu-Kwong; Chang, Raymond Chuen-Chung; Ma, Alvin Chun-Hang
ABSTRACT: 1-phenyl 2-thiourea (PTU) is a Tyr (tyrosinase) inhibitor that is extensively used to block pigmentation and improve optical transparency in zebrafish ( Danio rerio ) embryo. Here, we reported a previously undescribed effect of PTU on macroautophagy/autophagy in zebrafish embryos. Upon 0.003% PTU treatment, aberrant autophagosome and autolysosome formation, accumulation of lysosomes, and elevated autophagic flux were observed in various tissues and organs of zebrafish embryos, such as skin, brain, and muscle. Similar to PTU treatment, autophagic activation and lysosomal accumulation were also observed in the somatic tyr mutant zebrafish embryos, which suggest that Tyr inhibition may contribute to PTU-induced autophagic activation. Furthermore, we demonstrated that autophagy contributes to pigmentation inhibition, but is not essential to the PTU-induced pigmentation inhibition. With the involvement of autophagy in a wide range of physiological and pathological processes and the routine use of PTU in zebrafish research of autophagy-related processes, these observations raise a novel concern in autophagy-related studies using PTU-treated zebrafish embryos. Abbreviations: 3-MA: 3-methyladenine; Atg: autophagy-related; BSA: bovine serum albumin; CHT: caudal hematopoietic tissue; CQ: chloroquine; GFP: green fluorescent protein; hpf: hour-post-fertilization; Map1lc3/Lc3: microtubule-associated protein 1 light chain 3; NGS: normal goat serum; PtdIns3K: class III phosphatidylinositol 3-kinase; PTU: 1-phenyl 2-thiourea; RFP: red fluorescent protein; Sqstm1: sequestosome 1; tyr : tyrosinase.